(untitled) (GAIMS Journal of Medical Sciences, 2022)
Introduction Students’ attendance in medical colleges has been a topic for debate recently, because of declining class attendance in all phases of MBBS classes. It is important to understand the reasons for their absenteeism so that necessary actions may be taken to improve the attendance. This study was done to know the perception of faculty members regarding attendance of undergraduate medical students. Methodology A pre-validated questionnaire was circulated online to the faculty members of various medical colleges across India. The responses were tabulated and analyzed using descriptive analysis and chi-square test. Results 168 faculty members responded to the online questionnaire. 131 (78 %) respondents felt that in recent years the attendance of undergraduate medical students is showing a decreasing trend. There was no difference in the teachers’ perception of low attendance with respect to subject (clinical v/s non-clinical, 60 v/s 71, p = 0.38) or teaching experience (< 10 years v/s > 10 years, 46 v/s 85, p = 0.12). Preparation for PG entrance examination was the most perceived reason for students’ low attendance (68.6 %). 66.7 % respondents felt that there should be feedback sessions with students at regular intervals to know possible other causes of absenteeism. Conclusions The problem of low attendance of undergraduate medical students seems to be omnipresent (across subjects and colleges). Preparation for PG entrance examinations, no penalty for low attendance, lack of trained faculty members and no regulation on teaching are the major perceived reasons for low attendance. A robust faculty training program, modifying the content delivery to suit the students’ needs, contribution of Internal Assessment marks to University Assessment, contribution of UG marks for PG admissions and a strict attendance policy are the suggested remedies. A similar study is required to know the students’ point of view regarding the reasons for their absenteeism.